KETERAMPILAN SENAM LANTAI MELALUI PEMBELAJARAN KOOPERATIF DI MADRASAH TSANAWIYAH HIDAYATUL MUSLIMIN I - Khalilurrahman, Khalilurrahman; Haetami, Mimi; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem discussed in this study is whether by cooperative learning could improve floor gymnastic skills of students in class VIII Madrasah Tsanawiyah Hidayatul Muslimin 1. The purpose of this study is to improve floor gymnastic skills with cooperative learning of students in class VIII Madrasah Tsanawiyah Hidayatul Muslimin 1. The study was conducted with a descriptive qualitative method involving two variables, the independent variable is cooperative learning and the dependent variable is floor gymnastics skills. The subjects in this study were students of class VIII Madrasah Tsanawiyah Hidayatul Muslimin 1, totaling 33 students. This research technique uses tests and measurements, which is a test with a lattice measuring instrument measuring floor gymnastics skills. The Data analysis using percentages value. The results of this study indicate there is an increase in floor gymnastic skills with cooperative learning of students in Class VIII Madrasah Tsanawiyah Hidayatul Muslimin 1. This is evidenced by an increase in floor gymnastic skills of the students, when in the first cycle with an average value of 57.32 so the increase at 20.26%. Mean while the average value in the second cycle is 88.13, so the increase is 53.74%. Based on the results of research in this study, it could be suggested that the Physical Education teacher is expected to develop creativity and be more innovative in the learning process in an effort to improve student competency.Â Keywords: Cooperative Learning, Floor Gymnastic.